Corporate Governance and Capital Structure - Zahid, Rehan (Copernican Journal of Finance & Accounting, 2025)
This research presents a thorough examination of how corporate governance impacts capital structure, utilizing agency theory to explain the alignment of managerial and shareholder interests in financing choices. The factors such as board size, board independence, CEO duality have a positive effect on capital structure. Conversely, other factors like board gender, board meetings, board experience, Audit Committee Size have a negative correlation with capital structure. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework was utilized as the methodological approach. This process encompassed the identification, screening, eligibility assessment, and inclusion of relevant studies drawn from databases including Scopus, Web of Science, and Google Scholar. A total of 95 high-quality studies were scrutinized. The results offer insights into the influence of corporate governance on capital structure decisions in both developed and developing markets, providing significant implications for investors, analysts, and corporate stakeholders.